Molecular Complex of Amlodipine Besylate: Pharmaceutical Characterization and Stability Improvisation - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2023)
The study explains to increase the stability of a drug which is hygroscopic in nature (amlodipine besylate), by the molecular complex technique. The stability enhancement achieved using the cocrystallization method by the formation of a molecular complex. Saccharin as a coformer is formed by molecular complex. The selection of coformer was done based on the Hansen parameter where theoretical value was obtained which gave some coformer values and practically molecular complex study was carried out by the solubility method. No any interaction between amlodipine besylate and saccharin was confirmed by Fourier transform infrared (FTIR) and differential scanning calorimetry (DSC) studies. The stability-enhancing property of cocrystals was carried out by short-term accelerated stability studies. To perform stability analysis, few methods of cocrystallization were carried out. These cocrystals were evaluated by FTIR, DSC, and powder X-ray diffraction studies. It is concluded that the molecular complex of amlodipine besylate with sodium saccharin shows significant stability and highlights the use of cocrystallization in stability enhancement. The miscibility of drug and coformers as predicated by Hansen solubility parameter, can indicate cocrystal preparation. The resultant δ values of drug and coformers are compared and their solid state miscibility is expressed. The possibility of cocrystal formulation by krevelens is Δδ < 5 MP and Greenhalgh Δδ < 7 MP